Expression of the mRNA stability regulator Tristetraprolin is required for lactation maintenance in the mouse mammary gland - Goddio, Maria Victoria (2017)
Tristetraprolin (TTP), an mRNA-binding protein that negatively controls levels of inflammatory factors, is highly expressed in the lactating mouse mammary gland. To determine the biological relevance of this expression profile, we developed bi-transgenic mice in which this protein is specifically down-regulated in the secretory mammary epithelium in the secretory mammary epithelium during lactation. Our data show that TTP conditional KO mice produced underweight litters, possibly due to massive mammary cell death induced during lactation without the requirement of additional stimuli. This effect was linked to overexpression of inflammatory cytokines, activation of STAT3 and down-regulation of AKT phosphorylation. Importantly, blocking TNFa activity in the lactating conditional TTP KO mice inhibited cell death and similar effects were observed when this treatment was applied to wild-type animals during 48 h after weaning. Therefore, our results demonstrate that during lactation TTP wards off early involution by preventing the increase of local inflammatory factors. In addition, our data reveal the relevance of locally secreted TNFa for triggering programmed cell death after weaning.